Construction of photoswitchable urea-based multiple H-bonding motifs. (25th April 2023) - Chen, Lan-Yun; Wei, Lu; Hai, Yu; Liu, Li-Juan; Zhang, Kang-Da; Zhan, Tian-Guang
Abstract: In this paper, a series of photoactive urea-based multiple H-bonding motifs were rationally constructed by tethering the photoisomerizable azobenzene units aside to the urea groups of several typical urea-constituted H-bonding arrays. Taking the integrated azo units as photoswitches, their phototriggered E /Z isomerization can be used to reversibly manipulate the locking (with intramolecular H-bonds) and unlocking (without intramolecular H-bonds) of the urea H-bonding sites of these motifs, respectively. This feature enables the E / Z photoisomeric urea derivatives to exhibit switchable intermolecular H-bonding affinities, thus achieving unique photocontrolled self/hetero complementary multiple H-bonded dimerization upon irradiation by different light sources. Benefiting from the wide application of urea group, the development of such urea-based multiple H-bonding system with photoswitchable dimerization affinity is promising in providing a generally applicable approach for the construction of copious urea-based H-bonded supramolecular assembly systems and materials with photoregulable properties and functions. Graphical abstract: Image 1